KUALITAS PEPES IKAN LELE MENGGUNAKAN METODE STEAMING - Ziyadah, Lihayatil; Asnur, Lise (Diklat Review : Jurnal manajemen pendidikan dan pelatihan, 2024)
The dearth of Research on the effectiveness of steaming catfish to make pepes is what spurred this investigation. This study aims to identify the quality of catfish pepes by using the steaming method to identify the characteristic scent of fragrant basil leaves and their acidity, as well as the soft texture, reddish yellow color, and savory taste. They are adding details on the preparation of catfish pepes, fostering innovation in processed food items, and educating the public on the procedures catfish pepes, as seen from the aroma, taste, texture, and color. This kind of study is pure experimentation; it involves testing the quality of catfish pepes directly. Due to the fact that it solely looks at the influence of one variable that is, the impact of Quality of Catfish Pepes Using the Steaming Method. Three knowledgeable panelists will use an organoleptic test to evaluate the scent, texture, taste, and color of catfish pepes as part of this study phase. This study was conducted three times. After selecting the panelists, have the supplies and instruments ready to carry out the experiment. Considering the outcomes of the quality research of catfish pepes by conducting research 3 times with the same expert panelists, good catfish pepes quality results were obtained including catfish pepes color (reddish yellow), with an average of 4 (100%), catfish pepes texture (Soft) with an average of 4 (100%), catfish pepes aroma (basil and sour leaves) with an average of 4 (100%) and catfish pepes taste (savory) with an average of 4 (100%). Keywords: Quality of catfish pepes. Steaming method.